Right Ventricular Functional Improvement after Pulmonary Rehabilitation Program in Patients with COPD Determined by Speckle Tracking Echocardiography - Kanar,Batur Gonenc (2018)
Abstract Background: Although right ventricular (RV) dysfunction in pulmonary diseases has been associated with increased morbidity, tools for RV dysfunction identification are not well defined. Objective: The aim of this study was to evaluate the magnitude of RV dysfunction by means of speckle tracking echocardiography (STE) in patients with chronic obstructive pulmonary disease (COPD) and to investigate whether STE could be used as an index of RV improvement after a pulmonary rehabilitation (PR) program. Methods: Forty-six patients with COPD undergoing PR program and 32 age-sex matched healthy subjects were enrolled. RV function was evaluated at admission and after PR program by conventional two-dimensional echocardiography (2DE) and STE. In addition, exercise tolerance of subjects was evaluated using the six-minute walk test (6MWT). Results: COPD patients had worse RV function according to STE and 2DE as well. STE was more sensitive than conventional 2DE in determining RV improvement after PR program - RV global longitudinal strain (LS): 20.4 ± 2.4% vs. 21.9 ± 2.9% p < 0.001 and RV free wall LS: 18.1 ± 3.4% vs. 22.9 ± 3.7%, p < 0.001). RV free wall LS was directly related to distance walked at baseline 6MWT (r = 0.58, p < 0.001) and to the change in the 6MWT distance (6MWTD ∆) (r = 0.41, p = 0.04). Conclusions: We conclude that STE might be as effective as 2DE for evaluation of global and regional RV functions. STE may become an important tool for assessment and follow-up of COPD patients undergoing PR program to determine the relationship between RV function and exercise tolerance.